(untitled) (Plant Tissue Culture and Biotechnology, 2026)
The present study investigated the impact of varying doses of 2,4-dichlorophenoxyacetic acid (2,4-D) on friable callus induction and withaferin-A (WA) accumulation in Withania somnifera, popular as ‘Indian ginseng’. Friable calli cultures were established using variable doses of 2,4-D (1.0-5.0 mg/l). The 5.0 mg/l 2,4-D significantly enhanced callusing percentage (100%), fresh weight (795.0 mg), dry weight (DW) (99.0 mg), relative water content (709.0 %), as well as WA content (0.043 mg/100 g DW), demonstrating its superiority over other treatments. Pearson’s correlation analysis revealed strong positive associations among callus biomass traits and WA content, whereas days to callus induction showed weak correlations. Multivariate approaches, including correlation, principal component analysis and unweighted pair-group method with arithmetic mean clustering, effectively distinguished the 5.0 mg/l treatment as optimal. Overall, the findings establish a high-efficiency in vitro protocol for biomass and WA production in W. somnifera through friable callogenesis, offering valuable insights for large-scale phytochemical production and plant tissue culture applications. Plant Tissue Cult. & Biotech. 35(2): 257-265, 2025 (December)